Mineral and bone disorders in children with chronic kidney disease - Schmitt, Claus P.; Mehls, Otto (Nature reviews. Nephrology, 2011)
Control of bone and mineral homeostasis is essential in children with chronic kidney disease to prevent skeletal complications, achieve adequate growth and maintain cardiovascular health. This Review describes the pediatric aspects of chronic kidney disease mineral and bone disorder and discusses the potential of the latest therapeutic agents.
Gesehen am 12.10.2022